Identifying Strategies Programs Adopt to Meet Healthy Eating and Physical Activity Standards in Afterschool Programs. (August 2017) - Weaver, Robert G.; Moore, Justin B.; Turner-McGrievy, Brie; Saunders, Ruth; Beighle, Aaron; Khan, M. Mahmud; Chandler, Jessica; Brazendale, Keith; Randell, Allison; Webster, Collin; Beets, Michael W.
Background . The YMCA of USA has adopted Healthy Eating and Physical Activity (HEPA) Standards for its afterschool programs (ASPs). Little is known about strategies YMCA ASPs are implementing to achieve Standards and these strategies' effectiveness. Aims . (1) Identify strategies implemented in YMCA ASPs and (2) evaluate the relationship between strategy implementation and meeting Standards. Method . HEPA was measured via accelerometer (moderate-to-vigorous-physical-activity [MVPA]) and direct observation (snacks served) in 20 ASPs. Strategies were identified and mapped onto a capacity building framework ( S trategies T o E nhance P ractice [STEPs]). Mixed-effects regression estimated increases in HEPA outcomes as implementation increased. Model-implied estimates were calculated for high (i.e., highest implementation score achieved), moderate (median implementation score across programs), and low (lowest implementation score achieved) implementation for both HEPA separately. Results . Programs implemented a variety of strategies identified in STEPs. For every 1-point increase in implementation score 1.45% (95% confidence interval = 0.33% to 2.55%, p ≤ .001) more girls accumulated 30 min/day of MVPA and fruits and/or vegetables were served on 0.11 more days (95% confidence interval = 0.11-0.45, p ≤ .01). Relationships between implementation and other HEPA outcomes did not reach statistical significance. Still regression estimates indicated that desserts are served on 1.94 fewer days (i.e., 0.40 vs. 2.34) in the highest implementing program than the lowest implementing program and water is served 0.73 more days (i.e., 2.37 vs. 1.64). Conclusions . Adopting HEPA Standards at the national level does not lead to changes in routine practice in all programs. Practical strategies that programs could adopt to more fully comply with the HEPA Standards are identified.